Penerapan Konsep Demokrasi dalam Sistem Politik Indonesia Pasca-Reformasi - Rina Prasetya; Ahmad Zainudin (Gema Cendekia Institute, 2026)
The application of the concept of Pancasila Democracy in Indonesia’s post-reform political system is a relevant topic for understanding the country’s evolving political dynamics. Pancasila Democracy, as the ideological foundation of the state, holds that democracy must be implemented by prioritizing the values of Pancasila, which emphasize deliberation to reach consensus, social justice, and respect for human rights. This study aims to analyze the extent to which the concept of Pancasila Democracy has been applied in Indonesia’s political system following the reform era, by assessing changes in political structures and the practice of democracy. The approach employed in this study is legal-normative, analyzing legislation, political policies, and the implementation of democracy in post-reform Indonesian political practice. The results of the study indicate that although there have been efforts to integrate Pancasila values into the political system, the implementation of Pancasila democracy post-reform has often been hindered by practical political interests, weak social control, and disparities in political representation. This study concludes that to realize a substantive Pancasila democracy, it is necessary to strengthen political institutions, increase public participation, and ensure more effective oversight of the implementation of political policies in Indonesia.